Changes in telemonitored physiological variables and symptoms prior to exacerbations of chronic obstructive pulmonary disease. (January 2015) - Burton, Christopher; Pinnock, Hilary; McKinstry, Brian
We examined symptom scores and physiological measurements from patients who were using a pilot COPD telemonitoring service. Of 33 patients recruited to the study, 19 were monitored for longer than 200 days. We identified three patterns of exacerbation, which we termed discrete (n = 5), rolling (n = 9) and over-ridden (n = 4). The association between FEV1, pulse and SpO2 and total symptom score was examined using multilevel logistic regression. The intraclass correlation coefficient for the model was high (0.36) indicating that much of the variance was due to differences between individuals, rather than within individuals. Compared to baseline, at the onset of exacerbations (n = 172) the mean pulse rate increased from 87 to 94 /min and the mean SpO2 fell from 93.6 to 92.4%. However, physiological variables did not differentiate between exacerbations and isolated bad days (n = 150). Few patient records displayed clear patterns of normality and exacerbation. Clinicians selecting patients for telemonitoring should assess the patient's perception of variation in their symptoms and provide careful training and support whilst patients are learning to monitor their condition.